Estrategias para desarrollar habilidades del pensamiento en la educación superior: variables ocultas y estrategias - Aravena Gaete, Margarita; Ruete Zúñiga, David; Campos Soto, Natalia; Figueroa -Vargas, Andrea (Ariadna Ediciones, 2023)
The concern of a group of researchers together with the methods and strategies to teach people or rather students to think, motivated the creation of this book. Likewise, it seeks to explain the role played by the characteristics of the students described in demographic variables such as age, gender, etc., and hidden behavioral variables, which can be extracted from the execution of the evaluation instrument; such as response times, transition of the student's response in the different questions, etc., which also influence learning and cognitive action that are an important part of learning analysis, seen from different dimensions. Teaching to think through significant and real strategies is one of the premises of this book, which must be implemented according to explicit teaching, offer feedback and above all generate metacognition, with the conviction of being aware that the skills that we are developing especially, those that are complex to generate, are some of the variables to consider.